232k views
1 vote
Find the remainder when f(x) is divided by g(x) given that f(x) = 4x3 − 5x2 − 3x + 2 and g(x) = x − 3.

User Isagalaev
by
5.6k points

1 Answer

7 votes

Given:


f(x)=4x^3-5x^2-3x+2


g(x)=x-3

To find:

The remainder when f(x) is divided by g(x).

Solution:

According to remainder theorem, if f(x) is divides by (x-c), then remainder is f(c).

Using remainder theorem, if
f(x)=4x^3-5x^2-3x+2 is divides by
g(x)=x-3, then remainder is f(3).

Substitute x=3 in f(x).


f(3)=4(3)^3-5(3)^2-3(3)+2


f(3)=4(27)-5(9)-9+2


f(3)=108-45-7


f(3)=56

Therefore, the required remainder is 56.

User Zuljin
by
6.0k points